Monitoring Changes in Agricultural Landscapes of Central Europe, Hungary - Lemenkova Polina (Proceedings, Geoinformatics 2013, 2018)
This paper details changes in land cover types and vegetation distribution in tundra landscapes during the past two decades. The main method of the work is classification of the Landsat TM scenes for land cover change detection. The new approach of the current work is application of GIS and remote sensing tools for Bovanenkovo region, since there is no previous remote sensing and GIS-based studies performed in the same area focusing research problem of land cover changes. The research outcomes show changes in the land cover types in Bovanenkovo region in Yamal Peninsula during the past two decades. Analysing the classification results, the most evident trend in the vegetation changes in Yamal ecosystems is the overall increase of woody vegetation (willows) and decrease of peatlands and grasses. The changes in the structure of the Yamal ecosystems come through gradual amendments in species distribution and dominant classes, which now tends to be willows and shrub tundra. P. Lemenkova. "Monitoring Changes in Agricultural Landscapes of Central Europe, Hungary". In: Geoinformatics: Theoretical and Applied Aspects. Proceedings of 12th International Conference (Great Conference Hall of the National Academy of Sciences of Ukraine, May 13–16, 2013).